PENGARUH PELATIHAN, PERENCANAAN KARIR, DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DI KANTOR PELAYANAN PAJAK PRATAMA MEDAN TIMUR - Siahaan, Andri Christian; Matondang, Sofiyan; Sianturi, Marudut (LPPM Universitas Darma Agung, 2020)
ABSTRACT This study aims at finding the effect of training, career planning, and work discipline segmentally and simultaneously on employee performance at KPP Pratama Medan Timur. The population of this research is 102 employees working as staff employees (outside the Head of the Office, Head of Section, and Supervisor). The number of samples taken is 81 people using the Proportionate Stratified Random Sampling method. Data collection is using questionnaires, interviews, and documentation study while the data analysis technique used is the classical assumption test, multiple regressions, t test, F test, and the coefficient of determination. The results show that the better the employee training, the higher the performance; the better the employee career planning, the higher the performance; the better the work discipline, the higher the performance. The variables of training, career planning, and work discipline simultaneously have a significant effect on performance variables. The coefficient of determination Adjust R2 is 0.969. This means that variations in employee performance can be described by training, career planning, and work discipline by 96.9%, while the remaining 3.1% is explained by other factors, such as organizational culture, compensation, and other factors.